Education for Democracy in the Social Media Century - Knowles, Ryan Thomas; Camicia, Steven; Nelson, Lorissa (Research in Social Sciences and Technology- OpenED Network, 2023)
Social media has provided challenges and opportunities for education for democracy. There have always been structural elements of communication that are hidden and perpetuate inequalities. Social media has accelerated and empowered these hidden structures through algorithms. In this argumentative essay, we examine how critical media literacy can uncover hidden power structures and support education for democracy. Critical media literacy can help students identify exclusionary, inaccurate, missing, and polarizing elements of social media while examining and discussing issues and events. Seen through this lens, social media provides opportunities for education for democracy. Critical media literacy and education for democracy provide opportunities for increasing civic engagement and renewal.